PENDIDIKAN KARAKTER PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI MADRASAH TSANAWIYAH PERSIAPAN NEGERI 4 MEDAN - Hendri Fauzah; Mita Maharani (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
character education at Madrasah Tsanawiyah Negeri 4 Medan preparation is not optimal because the lesson plan includes several character values in the syllabus and lesson plans. In the implementation of learning, it applies twelve character values out of the eighteen character values contained in the character education development guidelines issued by the Ministry of National Education. The values applied in the implementation of learning such as religion, tolerance, discipline, democracy, curiosity, national spirit, love of the motherland, respect for achievement, love to read, care for the environment, care for the social and responsibility. For the evaluation of learning the assessment used is observation to observe student behavior, and assignments to determine student learning progress